Transcriptome and molecular regulatory mechanisms analysis of gills in the black tiger shrimp Penaeus monodon under chronic low-salinity stress - Li, Yun-Dong; Si, Meng-Ru; Jiang, Shi-Gui; Yang, Qi-Bin; Jiang, Song; Yang, Li-Shi; Huang, Jian-Hua; Chen, Xu; Zhou, Fa-Lin; Li, ErChao (Frontiers in Physiology, 2023)
Salinity is one of the main influencing factors in the culture environment and is extremely important for the survival, growth, development and reproduction of aquatic animals. In this study, a comparative transcriptome analysis (maintained for 45 days in three different salinities 30 psu, 18 psu and 3 psu) was performed by high-throughput sequencing of economic cultured P. monodon. P. monodon gill tissues from each treatment were collected for RNA-seq analysis to identify potential genes and pathways in response to low salt stress. A total of 64,475 unigenes were annotated in this study. 1,140 up-regulated genes and 1531 down-regulated genes were observed in the LC vs HC group and 1,000 up-regulated genes and 1,062 down-regulated genes were observed in the MC vs HC group. 583 DEGs in the LC vs HC group significantly mapped to 37 signaling pathways and 444 DEGs in the MC vs HC group significantly mapped to 28 signaling pathways. These pathways were significantly associated mainly with signal transduction, immunity and metabolism. These results suggest that low salt stress may affect regulatory mechanisms such as metabolism, immunity, and signal transduction in addition to osmolarity in P. monodon. This study provides some guidance for understanding the low-salt domestication culture of P. monodon.